INTEGRATED MYCOTOXIN MANAGEMENT IN THE BRAZILIAN CORN CHAIN FOR POULTRY FEED - Brabet, Catherine; Salay, Elisabete; Freitas-Silva, Otniel; Florindo Alves, Alexandre; Machinski Jr., Miguel; Azevedo Vargas, Eugenia; Zakhia-Rozis, Nadine (Science & Technology Journals, 2005)
This article presents the research activities carried out in Brazil within the framework of the INCO-DEV Mycotox project. This co-operation project funded by the European Commission (ICA4-CT-2002-10043) aims at developing an integrated quality management system for the control of mycotoxins in the corn and wheat production chains in Latin America South Cone countries (Brazil, Chile, Argentina, and Uruguay). The project involves institutional partners as well as key actors of the cereal production chains. The approach chosen consists in applying the HACCP (Hazard Analysis Critical Control Point) principles to the entire agri-food chain within the framework of case studies carried out in the South Cone countries involved in the project, taking into account not only the technical issues but also the socio-economic issues. This approach will help validate and implement technical and organizational itineraries adapted to the local contexts for controlling mycotoxin contamination. In addition, the activities emphasise the development and validation of effective analytical methods for mycotoxin determination (chromatographic methods, alternative techniques such as near infrared spectrometry and the mini-column-based Toximet procedure for routine on-field assessment). Brazil is the third largest corn producer in the world. More than 70% of the national production is used for animal feed, most of which poultry. This is the reason why the corn production chain for poultry feed was selected as the case study to be conducted in this country. The integrated quality management system developed will be generic, and will be able to apply to other quality criteria and/or agri-food chains.